Altitude as a key environmental factor shaping microbial communities of tea green leafhoppers (Matsumurasca onukii) - Yong Zhang; Song Liu; Xue-yu Huang; Hua-bin Zi; Tian Gao; Rui-jie Ji; Juan Sheng; Dian Zhi; Ying-lao Zhang; Chun-mei Gong; Yun-qiu Yang (Microbiology Spectrum, 2023)
ABSTRACT The tea green leafhopper, Matsumurasca onukii Matsuda, is the most destructive insect pest of tea plantations in East Asia. While several microbes in M. onukii have been characterized, the microbial community compositions in wild M. onukii populations and the environmental factors that shape them are mostly unknown. In this study, M. onukii populations were collected from major tea growing regions in China. Following high-throughput sequencing of 16S rRNA gene fragments for bacteria and the internal transcribed spacer region for fungi, association analyses were performed within the microbial communities associated with M. onukii and their environmental drivers. We found that the bacterial community structures differed in various regions, and the abundance of dominant bacteria such as Wolbachia, Pseudomonas, Acinetobacter, Pantoea, Enterobacter, and Methylobacterium varied widely. Moreover, wild populations of M. onukii can be infected with facultative symbionts from six genera (Wolbachia, Rickettsia, Asaia, Serratia, Arsenophonus, and Cardinium) with divergent relative abundances. Correlation analysis indicated that altitude was a key environmental factor that shaped bacterial communities of M. onukii. Furthermore, longitude, temperature, and rainfall are also significantly correlated with the bacterial communities. The fungal communities of M. onukii populations were dominated by Ascomycota and Basidiomycota, of which most genera are considered to be plant endophytes or plant pathogens, such as Cladosporium, Fusarium, Alternaria, and Gibberella. We demonstrated that M. onukii carry a complex and variable microbial community, which is influenced by altitude as well as climate-related factors. Our results provide novel insights into the bacteria and fungi of M. onukii. IMPORTANCE Host-associated microbial communities play an important role in the fitness of insect hosts. However, the factors shaping microbial communities in wild populations, including environmental factors and interactions among microbial species, remain largely unknown. The tea green leafhopper has a wide geographical distribution and is highly adaptable, providing a suitable model for studying the effect of ecological drivers on microbiomes. This is the first large-scale culture-independent study investigating the microbial communities of M. onukii sampled from different locations. Altitude as a key environmental factor may have shaped microbial communities of M. onukii by affecting the relative abundance of endosymbionts, especially Wolbachia. The results of this study, therefore, offer not only an in-depth view of the microbial diversity of this species but also an insight into the influence of environmental factors.